2019
DOI: 10.1212/wnl.0000000000008552
|View full text |Cite
|
Sign up to set email alerts
|

Factors and measures predicting external CSF drain-associated ventriculitis

Abstract: ObjectiveTo determine the diagnostic value of clinical factors and biochemical or microbiological measures for diagnosing a drain-associated ventriculitis, we summarized the available evidence.MethodsWe performed a systematic review and meta-analysis of studies of patients with external ventricular CSF drains who developed drain-associated ventriculitis by searching MEDLINE, EMBASE, and CENTRAL electronic database. We reported the occurrence of abnormal test results in patients with and without drain-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 61 publications
2
50
0
Order By: Relevance
“…The latter is the most common cause of EVD-associated infection [8]. Causative bacterial pathogens are skin commensals such as Gram-positive coagulase-negative staphylococci, Staphylococcus aureus, and Gram-negatives Escherichia coli, Acinetobacter spp., and Klebsiella spp [4]. Many bacterial pathogens are able to produce a biofilm on the drain hampering effective antimicrobial therapy [9,10].…”
Section: Incidence and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is the most common cause of EVD-associated infection [8]. Causative bacterial pathogens are skin commensals such as Gram-positive coagulase-negative staphylococci, Staphylococcus aureus, and Gram-negatives Escherichia coli, Acinetobacter spp., and Klebsiella spp [4]. Many bacterial pathogens are able to produce a biofilm on the drain hampering effective antimicrobial therapy [9,10].…”
Section: Incidence and Pathogenesismentioning
confidence: 99%
“…Symptoms of infection may be masked by the primary neurological condition and a neurosurgical intervention itself may cause a sterile inflammatory response further hampering the diagnostic process of ventricular catheter-associated infections [2]. These diagnostic dilemmas may result in delayed treatment of patients with bacterial infection as well as unnecessary antimicrobial therapy [3,4]. In this narrative review, we describe the diagnostic accuracy of clinical factors and biochemical and microbiological measures, discuss preventive measurements, and provide insight into the treatment approach of patients with external ventricular catheter-associated infection.…”
Section: Introductionmentioning
confidence: 99%
“…VM is an acute complication associated with neurosurgery and may lead to permanent adverse outcomes if not managed properly (Beer et al, 2008). The incidence of VM rates was reported to range from 2 to 45% (Dorresteijn et al, 2019), and the predisposing factors for VM include non-adherence to rigid insertion and maintenance protocols, leakage of CSF, catheter irrigation, and the frequency of EVD or LD manipulation. Meanwhile, our study indicated the same results in cVM and sVM (39 and 49 of 102 patients, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…External ventricular drains (EVDs) and, in some specific cases, lumbar drains (LDs) are essential to drain cerebrospinal fluid (CSF) and control intracranial pressure after neurosurgery (Brain Trauma Foundation et al, 2007;Carney et al, 2017). One of the risks surrounding the placement and maintenance of catheters is the infection of cerebrospinal fluid (CSF), with infection rates ranging from 2 to 45% (Lozier et al, 2008;Scheithauer et al, 2010;van de Beek et al, 2010;Dorresteijn et al, 2019). EVD/LDassociated ventriculitis and meningitis (VM) are correlated with high rates of morbidity and mortality, significantly prolonged lengths of hospitalization (LOS), elevated hospital costs, and negatively affected prognosis (Citerio et al, 2015;Hussein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Once hydrocephalus has occurred, it is probable to miss the best opportunity to rescue the patients by placing EVD. However, if the EVD is placed in advance, it may increase the risk of infection and supratentorial hemorrhage [9][10][11][12]. Therefore, there is still debate about when to place the EVD on TICH.…”
Section: Introductionmentioning
confidence: 99%